Model Pembelajaran Pendidikan Agama Islam Pada Masa Pandemi Corona di RA Taam Adinda Desa Kepatihan Menganti Gresik - Ramdhan, Tri Wahyudi; Syaikhon, Muhammad; Saleh, Nanang Rokhman; Azim Abdurakhmonovich, Yuldashev (AL MURABBI, 2024)
RA TAAM Adinda is an early childhood education institution that prioritized Islamic values in learning during the COVID-19 pandemic. This research aims to determine the Islamic education values instilled in early childhood at RA TAAM Adinda in the village of Kepatihan Menganti Gresik, as well as its learning models. This study is field research with a descriptive qualitative approach. Data collection techniques were carried out through observation, in-depth interviews, and documentation. Data analysis was conducted in three stages: data reduction, data presentation, and conclusion/verification. The findings of this study can be summarized that the Islamic values taught to early childhood at RA TAAM Adinda Menganti Gresik are values of faith, Sharia, and akhlak. The Islamic Education learning model during the COVID-19 pandemic at RA TAAM Adinda is carried out through active learning approaches and enjoyable learning approaches. The methods used include the playing method, storytelling method, exemplary method, habituation method, demonstration method, and question-answer method using video calls, sending videos in WhatsApp groups, and Zoom. Meanwhile, the Islamic Education learning procedure is carried out through planning, implementation, and evaluation stages.